Aplikasi Virtual Reality Atom Kimia di Seamolec - Inna Novianty; Walidatush Sholihah; Yudawan Aditama (MATRIK : Jurnal Manajemen, Teknik Informatika dan Rekayasa Komputer, 2020)
This study aims to design distance learning media in the form of virtual reality. The theme of application is chemical atoms. The use of VR in education is expected to be able to improve the learning process to be more interesting because Z generation is more interested in technology-based learning. This Virtual Reality application of chemical atoms (VRChemistry) contains a list of atoms in the periodic table. The method used in this research is Interactive Multimedia System of Design and Development (IMSDD). This method was developed by Dastbaz (2003). The stages in this method are: system requirements; design consideration; implementation, and evaluation. VRChemistry displays the main room menu as the main menu which will set the user to enter the virtual world of chemical atoms. This page displays the elements contained in the periodic table along with details of the selected elements, then see about the application or exit the application. The results of this study are multimedia applications in the form of virtual reality about chemical atoms. This application is useful for distance learning.